Between Immediacy and Articulation: Rethinking Non-Conceptuality in Dignāga Epistemology - Pankaj Srivastava (Transpublika Publisher, 2026)
This research paper critically re-examines non-conceptual cognition (nirvikalpaka-pratyakṣa) in Dignāga’s epistemology, focusing on the distinction between conceptual and non-conceptual knowledge within pramāṇavyavasthā. Dignāga explains that “pratyakṣaṃ kalpanāpoḍham” refers to perception devoid of conceptual constructs (kalpanā) that perceives the svalakṣaṇa. In contrast, inference (anumāna) depends on conceptual determination (vikalpa) and exclusion (apoha). The binary of two separate realms creates an epistemic hierarchy that views non-conceptual awareness as more immediate and ultimately more reliable. This paper argues that although the hierarchy between non-conceptual and conceptual knowledge is epistemologically justified, it may obscure Buddhism’s ethical and liberation aims, which focus on duḥkha, pratītyasamutpāda, and nirvāṇa. The discussion emphasizes two main points: First, it presents a relational view of cognition that combines epistemic analysis with ethical intent, linking Dignāga’s ideas to the broader Buddhist goal of nirvāṇa. Second, it proposes a phenomenological framework that links immediacy to articulation, fostering a relational understanding of cognition that avoids rigid dualism and highlights Buddhism’s ethical and emancipatory aims.